2020
DOI: 10.5935/1518-0557.20200028
|View full text |Cite
|
Sign up to set email alerts
|

HCG trigger versus GnRH agonist trigger in PCOS patients undergoing IVF cycles: frozen embryo transfer outcomes

Abstract: Objective: The use of Gonadotrophin releasing hormone agonist (GnRHa), with freeze-all strategy followed by frozen embryo transfer (FET) has been found to eliminate the risk of ovarian hyperstimulation syndrome (OHSS) in women with polycystic ovarian syndrome (PCOS) undergoing IVF cycles. However, physicians still hesitate to routinely use GnRHa as a trigger, replacing human chorionic gonadotrophin (hCG), for concerns of compromised cycle outcome. We aimed to evaluate outcomes following the transfer of embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
0
3
2
Order By: Relevance
“…A recent meta analysis concluded that there was a statistically significant higher clinical pregnancy rate after the transfer of embryos obtained from the GnRHa group in comparison to that from the HCG group in frozen-thawed cycles, that might be linked to a higher number of oocytes retrieved, greater maturity, better fertilization, greater number of high quality embryos and a higher number of blastocysts gained in the GnRHa group in comparison to the HCG group. 13 Moreover, in the present study, there was no statistically significant difference between HCG triggering group and GnRH agonist triggering group as regard the quality of embryos nor the number of transferred embryos.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…A recent meta analysis concluded that there was a statistically significant higher clinical pregnancy rate after the transfer of embryos obtained from the GnRHa group in comparison to that from the HCG group in frozen-thawed cycles, that might be linked to a higher number of oocytes retrieved, greater maturity, better fertilization, greater number of high quality embryos and a higher number of blastocysts gained in the GnRHa group in comparison to the HCG group. 13 Moreover, in the present study, there was no statistically significant difference between HCG triggering group and GnRH agonist triggering group as regard the quality of embryos nor the number of transferred embryos.…”
Section: Discussioncontrasting
confidence: 51%
“…So, in IVF cycles for PCOS women, a trigger by HCG should be substituted by a trigger by GnRHa with vitrification of all embryos followed by frozen embryo transfer. 6 In the current study, there was no statistically significant difference between GnRH agonist and HCG triggering regarding the quality of oocytes.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Embryos were graded using the Istanbul consensus [35] and grade 1 was a top-quality cleavage stage embryo in this study. This group also demonstrated that among the same cohort of 210 patients, pregnancy rates following frozen ETs after use of an agonist trigger are comparable or improved compared to those with the use of hCG [36 ▪ ]. There were 170 subsequent FET cycles in the GnRHa group and 195 FET cycles in the hCG trigger group.…”
Section: Trigger Of Final Follicular Maturationmentioning
confidence: 80%
“…27 As the risk of OHSS is due to the effect of hCG, 28 using GnRH agonist protocols to trigger ovulation and reducing hCG usage can reduce OHSS in the GnRH antagonist protocol. 29,30 For our center, there were only a few mild OHSS cases in the two groups. Those patients with a high potential risk of OHSS occurrence on embryo transfer day will not have fresh cycle implementation.…”
Section: Discussionmentioning
confidence: 96%